PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ALAT UKUR SISWA KELAS X PROGRAM STUDI MEKANIK OTOMOTIF DI SMK TAMANSISWA JETIS YOGYAKARTA TAHUN PELAJARAN 2014/2015 - Alfian Mintarta; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to find motivation; 1) improving student learning a measuring instrument in a class x through a method of inkuiri; 2) improving student learning outcomes a measuring instrument in a class x inkuiri study program through a method of vocational skills mechanical automotive Tamansiswa Jetis Yogyakarta years lessons 2014 and 2015 .A kind of this research included in the category of research the act of class (classroom action research). In this research, class x vocational students Tamansiswa Jetis Yogyakarta were 30 students in each class. Data collection techniques using tests, observation and poll. Poll here used to measure the interest of students learning to a measuring instrument. Tests using about learning to know the value of intermediate a measuring instrument. The technique of analysis of data using tests and observation that be done every cycle, 1 start from the cycle, 2 and 3, by doing the analysis to determine the average test scores, increasing (gain).Research result indicates that; (1) the learned in the method inkuiri using measuring instrument for each cycle shows increasing significantly; (2) the learned in the method inkuiri using measuring instrument for each cycle shows increasing significantly; (3) the increase in the motivation and learning measuring instrument graders X SMK Tamansiswa Jetis are the lessons 2014 - 2015.